3D‐Structured Monoliths of Nanoporous Polymers by Additive Manufacturing. Issue 5 (20th February 2020) - Hock, Sebastian; Rose, Marcus
Abstract: Recent advances in 3D printing provide great opportunities for the utilization of functional materials in chemical engineering and heterogeneous catalysis. In this work cylindrical monoliths with varying geometries of transport channels are designed and printed by a fused deposition modeling (FDM) 3D printer from thermoplastic polymers. Their hydrodynamic characteristics are investigated. For a proof of concept composite monoliths of microporous hyper‐crosslinked polymers (HCP) are printed. They contain up to 40 wt % of HCP with an accessible specific surface area of up to 171 m 2 g −1 . Abstract : Four different monoliths are designed and 3D printed to fit a laboratory‐scale tubular reactor. The hydrodynamic characteristics of the monoliths are measured. With microporous hyper‐crosslinked polymers (HPC) as filler composite filaments are printed with up to 40 wt % HCP, resulting in monoliths with hierarchical porosity.